Her secret vows with the viking - Rodi, Sarah (Harlequin historicals., 2024)
A year ago, Viking Stefan’s clandestine marriage to Saxon maiden Ædwen was torn apart by the shocking discovery that her father murdered his family. Unable to forgive his wife for hiding the truth, Stefan left. Until word reaches him that Ædwen is about to wed again… Forced to marry at her father’s command, Ædwen’s stunned when Stefan bursts through the church doors and announces that she’s already wed—to him! As the warrior steals her away, passion reignites, but can Ædwen ever trust him again, when Stefan left her alone, devastated—and carrying his baby…!